PATOMEKANISME PENYAKIT GAGAL JANTUNG KONGESTIF - Rachma, Lailia Nur (El-Hayah : Jurnal Biologi, 2014)
Heart failure is a clinical syndrome characterized by abnormalities in the structure or function of the heart, resulting in inability of heart to pump blood to meet the metabolic needs of the body tissue. Heart failure is characterized by clinical manifestations such as circulation congestion, tightness, fatigue, and weakness. Heart failure is a major problem in industrial and developing Country. Currently, the incidence and prevalence of heart failure tends to increase, it is also accompanied by an increase in mortality of heart failure cases. In the United States, 1 million patients hospitalized due to heart failure cases, which contribute to 50,000 deaths each year. While the number of visits to the hospital due to heart failure estimated at 6.5 million. Heart failure prognosis is generally poor despite the patients accepted adequate therapy. From the data obtained, only about 35% of male patients and 50% female patients who survived after the onset of acute heart failure. Generaly, the data obtained high mortality are occurs in patients with grade IV (presence of symptoms at rest) is about 30-70%, grade III (presence of symptoms with mild activity) 10-20%, class II (presence of symptoms when the activity being 5-10 %). Higher mortality was found in older patients, men, patients with reduced ejection fraction, and in patients with coronary disease. Once someone is suffering from heart failure, then he shall bear the very high cost. In America, the cost of issued for heart failure therapy between 15-40 trillion US$. In this review, we will discuss about pathomechanism of heart failure. So it is expected to be a reference to the diagnosis of patients with heart failure, which is expected to be recognized early on that could ultimately improve the quality of heart failure patient life, and reduce the number of mortality due to heart failure